Evaluation of Transient Ischemic Dilation (TID) Ratio in Gated SPECT Myocardial Perfusion Imaging (MPI) with Pharmacological Stress Agents - Ahmed, Rezoana; Rahman, Sharmin; Begum, Shamim Momtaz Ferdousi; Hussain, Raihan (Bangladesh Journal of Nuclear Medicine, 2019)
Objectives: Transient ischemic dilation (TID) refers to an apparent increase in the size of the left ventricular cavity on stress myocardial perfusion imaging compared to rest imaging. This study was performed to correlate the value of TID ratio in gated SPECT MPI in Coronary Artery Disease (CAD). Patients & Methods: Seventy-four suspected or known CAD patients underwent MPI performed with Tc-99m sestamibi. Single day stress - rest protocol with pharmacological stress was followed, according to established practicing protocol of NINMAS. A statistical analysis was carried out by using the Statistical Package for Social Sciences version 20.0 for Windows (SPSS Inc., Chicago, Illinois, USA). Student t-test was used for continuous variables. Chi-square test used to compare categorical data. P values <0.05 was considered as statistically significant. Results: Among 74 patients, 63(85.1%) were male and 11(14.9%) were female. The mean age found to be 53.8±10.5 years. Majority (90.5%) patients had hypertension, 45(60.8%) had diabetic mellitus and 39(52.7%) had dyslipidemia in blood lipid profile, 44(59.5%) were past smoker. The mean ejection fraction was 44.6±14.6 percent. The mean abnormal TID ratio was 1.25 ± 0.35 in patients having abnormal MPI findings and 1.03±0.21 in having normal MPI findings. The difference was statistically significant (p<0.05) between two groups. It was also observed that in three cases having normal MPI had high TID ratio.Among the patients with TID ratio >1.19, 24(64.9%) patients were in MVD group and 13(92.9%) were in SVD group. Whereas among the patients with TID ratio<1.19, 13(35.1%) were in MVD group and 1(7.1%) were in SVD group. The difference was statistically significant (P<0.05) between two groups. The mean TID ratio was 1.08±0.21 in single vessel disease and 1.24±0.26 in multiple vessel disease. The difference was also statistically significant (p<0.05) between two groups. Conclusion: This study suggests that the TID ratios could provide incremental diagnostic information to standard myocardial perfusion analysis for the identification of severe and extensive disease in patients with suspected or known CAD. Bangladesh J. Nuclear Med. 21(2): 77-80, July 2018